Determination of cholesterol oxides by gas chromatography‐flame ionization detection/mass selective detection and their occurence in lanolin‐containing cosmetics and ointments. (24th August 2015) - Schrack, S.; Hohl, C.; Schwack, W.; Niederer, M.; Roux, B.
Synopsis: Objective: Cholesterol oxides (COPs) are thought to be of toxicological relevance in cholesterol‐containing foods. For cholesterol‐containing cosmetics and the like, no information is available up to this date. Therefore, the first of two main aims of this study was to develop and validate a method for determining COPs in lanolin‐containing cosmetics such as lipsticks and fatty creams as well as in nipple ointments. The second aim was to study the occurrence of COPs and their concentration levels in the respective product classes. Methods: The procedure is based on a published method for food comprising some necessary modifications. Sample preparation consisted of transesterfication, solid‐phase extraction and silylation of target compounds. Separation of the derivatized COPs and their quantification were performed with gas chromatography (GC) using a flame ionization detector (FID) or a mass spectrometer (MS). Results: The successful validation and the trouble‐free application during the market survey showed that the method was fit for purpose. Total COP levels found were in the low per cent range (up to 3%) and surprisingly high, being many orders of magnitude higher than those published for foods. Conclusion: To our knowledge, we present for the first time a method for the determination of COPs in non‐food consumer products. Furthermore, our study demonstrates that lanolin‐containing cosmetics may be an additional exogenous source of COPs. We further show evidence, that at least part of the COPs are already formed on the sheep's wool.